Emergence of argumentation in elementary science classrooms - Qingna Jin; Mijung Kim (Canadian Society for Studies in Education, 2020)
Scientific argumentation can emerge naturally and spontaneously where students with diverse backgrounds and knowledge interact in classrooms. As research on argumentation as an emergent phenomenon has been limited in school science education, this paper particularly aims to understand how elementary students' argumentation emerges and develops through problem solving process. A qualitative case study was conducted in a fifth-/sixth- grade science classroom in Canada over a 4-month period. Data resource included classroom video recording, interviews, and artifacts from classroom activities. It was found that student argumentation often occurred spontaneously when students explicitly questioned about the rationales of each other's' ideas. Teacher scaffolding in problem-solving contexts and students' appreciation of peers' different ideas in collaborative contexts positively influenced scientific argumentation to emerge and develop.